UK consensus definitions for necrotising otitis externa: a Delphi study. Issue 2 (20th February 2023) - Hodgson, Susanne H; Khan, Maha M; Patrick-Smith, Maia; Martinez-Devesa, Pablo; Stapleton, Emma; Williams, O Martin; Pretorius, Pieter; McNally, Martin; Andersson, Monique I
Abstract : Objective: To establish consensus definitions for necrotising otitis externa (NOE) to facilitate the diagnosis and exclusion of NOE in clinical practice and expedite future high-quality study of this neglected condition. Design: The work comprised of a systematic review of the literature, five iterative rounds of consultation via a Delphi process and open discussion within the collaborative. An expert panel analysed the results to produce the final outputs which were shared with and endorsed by national specialty bodies. Setting: Secondary care in the UK. Participants: UK clinical specialists practising in infection, ear nose and throat (ENT) surgery or radiology. Main outcome measures: Definitions and statements meeting the following criteria were accepted: (a) minimum of 70% of respondents in agreement or strong agreement with a definition/statement AND (b) <15% of respondents in disagreement or strong disagreement with a definition/statement. Results: Seventy-four UK clinicians specialising in ENT, Infection and Radiology with a special interest in NOE took part in the work which was undertaken between 2019 and 2021. The minimum response rate for a Round was 76%. Consensus criteria for all proposed case definitions, outcome definitions and consensus statements were met in the fifth round. Conclusions: This work distills the clinical opinion of a large group of multidisciplinary specialists from across the UK to create practical definitions and statements to support clinical practice and research for NOE. This is the first step in an iterative process. Further work will seek to validate and test these definitions and inform their evolution.